2008
DOI: 10.1002/jbm.a.32004
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of drug‐loaded electrospun aligned fibrous threads for suture applications

Abstract: In this work, drug-loaded fibers and threads were successfully fabricated by combining electrospinning with aligned fibers collection. Two different electrospinning processes, that is, blend and coaxial electrospinning, to incorporate a model drug tetracycline hydrochloride (TCH) into poly(L-lactic acid) (PLLA) fibers have been used and compared with each other. The resulting composite ultrafine fibers and threads were characterized through scanning electron microscopy, transmission electron microscopy, Fourie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
116
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(124 citation statements)
references
References 116 publications
(225 reference statements)
7
116
1
Order By: Relevance
“…Bosworth et al reported a way to prepare uniaxially aligned fiber bundles by collecting fibers in a liquid reservoir, and scaffolds mimicking the hierarchical tendon structure could be fabricated using these bundles for tendon regeneration [20]. He et al obtained relatively long and aligned fiber bundles for suture application by using a rotating round disc with high rotation speed as the collector [21].…”
Section: Electrospun Fibrous Bundlementioning
confidence: 99%
See 1 more Smart Citation
“…Bosworth et al reported a way to prepare uniaxially aligned fiber bundles by collecting fibers in a liquid reservoir, and scaffolds mimicking the hierarchical tendon structure could be fabricated using these bundles for tendon regeneration [20]. He et al obtained relatively long and aligned fiber bundles for suture application by using a rotating round disc with high rotation speed as the collector [21].…”
Section: Electrospun Fibrous Bundlementioning
confidence: 99%
“…Bioactive agents or drugs encapsulated into electrospun nanofibers show steady release characteristics. A model drug tetracycline hydrochloride (TCH) encapsulated into PLLA fibers have been used to fabricated core-shell fibers through coaxial electrospinning [21]. In vitro release study indicated that threads made from the core-shell fibers could suppress the initial burst release and provide a sustained drug release useful for administering growth factor or other therapeutic drugs.…”
Section: Application Of Electrospun Fibers In Drug Deliverymentioning
confidence: 99%
“…The second is the creation of more complex nanostructures (such as core-shell and Janus systems, and combinations thereof) in order to yield materials with improved functional performance [23][24][25][26]. In the biomedical field, if a drug reservoir could be formed as the core of electrospun core-shell fibers, then new fiber-based nanoscale drug depots could be created, such as an electrospun suture [27]. These would differ significantly from the nanoparticle-based depots which have mainly been explored to date.…”
Section: Introductionmentioning
confidence: 99%
“…One of the attractive aspects of the electrospinning technique is the flexibility of the process and that the morphology of the fibres can be readily varied by changing processing conditions, including producing fibres with solid, porous and coreshell morphologies. Solid and porous fibres can be obtained by changing the processing condition such as types of solvents and humidity whilst the core-shell morphology is obtained through setting up the inner and outer needle during electrospinning [2,9,10,27]. In its most basic form, electrospun webs are produced from a relatively simple process that consists of a pipette to hold a dissolved polymer solution, a high voltage source and a collector.…”
Section: Introductionmentioning
confidence: 99%